The 'full liberty of public writers': special treatment of journalism in English law - Danbury, R; Richard Danbury (2014)
This thesis investigates whether institutional journalism should receive special treatment at the hands of the law. Special treatment encompasses the affording of benefits to and the imposition of liabilities on journalistic institutions and the individuals who work for them. The arguments against special treatment are pragmatic and theoretical: pragmatic arguments emphasise, inter alia, the difficulty of providing a definition of journalism, and theoretical arguments emphasise the difficulty in explaining why special treatment can be coherent. The former can be addressed by describing how special treatment is already afforded to institutional journalism, both liabilities and benefits, to individuals and institutions, and showing that some of the problems foreseen by the pragmatic arguments have not proved as difficult as they appear. The arguments that special treatment is incoherent can be addressed by arguing that the credibility and assessability of institutional journalism still provide a prima facie rationale for special treatment irrespective of the rise of public speech on the Internet, when combined with the integral nature of journalism to democracy. Two basic arguments are advanced why this is so. The first, the free speech values argument, is a consequentialist account that holds that special treatment is appropriate when (or because) institutional journalism contributes to free speech values. It is attractive, but presents difficulties, both when considered in the abstract and when applied to the free speech value of democracy. The second, a rights-based argument, based on the notion that freedoms of speech and of the Press are distinguishable, can be based on either on Dworkin’s theory of rights as trumps or Raz’s theory of rights as interests. Raz’s account is preferable, as it complements the free speech values thesis in explaining the coherence of special treatment.